Cigarette and Cardiorespiratory Fitness - Tarwoto Tarwoto (Journal of Social Science, 2022)
Cigarettes are substances that contain various ingredients that have a negative impact on the body for both active and passive smokers. This study aims to investigate the effect of smoking habits on cardiorespiratory fitness. The design of the analysis used a crosectional sampling method with a sample of 100 online motorcycle taxi drivers. Data collection through questionnaires and measurements of cardiorespiratory fitness. Cardiorespiratory fitness measurements were carried out by the respondents, running for 15 minutes, and the results were converted to the Heywood scale. The results showed that of the 100 respondents, 55 people (55%) smoked and 45 people (45%) did not smoke. The statistical analysis revealed a significant relationship between smoking behavior and cardiorespiratory fitness in online motorcycle taxi drivers, with a value of p = 0.004 (α <0.05). The recommendations in this study are for smoking behavior factors to be considered in determining the degree of cardiorespiratory fitness.